Cell cycle activation in thyroid hormone-induced apoptosis and stem cell development during Xenopus intestinal metamorphosis - Tanizaki, Yuta; Shibata, Yuki; Na, Wonho; Shi, Yun-Bo (Frontiers in Endocrinology, 2023)
Amphibian metamorphosis resembles mammalian postembryonic development, a period around birth when many organs mature into their adult forms and when plasma thyroid hormone (T3) concentration peaks. T3 plays a causative role for amphibian metamorphosis. This and its independence from maternal influence make metamorphosis of amphibians, particularly anurans such as pseudo-tetraploid Xenopus laevis and its highly related diploid species Xenopus tropicalis, an excellent model to investigate how T3 regulates adult organ development. Studies on intestinal remodeling, a process that involves degeneration of larval epithelium via apoptosis and de novo formation of adult stem cells followed by their proliferation and differentiation to form the adult epithelium, have revealed important molecular insights on T3 regulation of cell fate during development. Here, we review some evidence suggesting that T3-induced activation of cell cycle program is important for T3-induced larval epithelial cell death and de novo formation of adult intestinal stem cells.